Dolichognatha bannaensis new species, a six-eyes tetragnathid spider from China (Araneae, Tetragnathidae) - Wang, Lu-Yu; Zhang, Zhi-Sheng; Peng, Xian-Jin (Zootaxa, 2020)
Almost all of the tetragnathid spiders have eight eyes, while two Dolichognatha species, D. longiceps (Thorell, 1895) (Sunil Jose 2014: 474, figs 1A–B) and D. junlitjri (Barrion-Dupo & Barrion, 2014) (Barrion-Dupo & Barrion 2014: 196, figs 1A–B) have six eyes (PME absent). They were originally assigned to Prolochus Thorell, 1895, which was synonymized with Dolichognatha O. Pickard-Cambridge, 1869 by Levi (1981), and reaffirmed by Kallal & Hormiga (2018) after a multi-loci phylogenetic analysis.